Simultaneous AFM Investigation of the Single Cardiomyocyte Electro-Chemo-Mechanics During Excitation-Contraction Coupling - Caluori, Guido; Raiteri, Roberto; Tedesco, Mariateresa (Methods in molecular biology, 2019)
The cardiac excitation-contraction coupling is the cellular process through which the heart absolves its blood pumping function, and it is directly affected when cardiac pathologies occur. Cardiomyocytes are the functional units in which this complex biomolecular process takes place: they can be represented as a two-stage electro-chemo and chemo-mechanical transducer, along which each stage can be probed and monitored via appropriate micro/nanotechnology-based tools. Atomic force microscopy (AFM), with its unique nanoresolved force sensitivity and versatile modes of extracting sample properties, can represent a key instrument to study time-dependent heart mechanics and topography at the single cell level. In this work, we show how the integrative possibilities of AFM allowed us to implement an in vitro system which can monitor cardiac electrophysiology, intracellular calcium dynamics, and single cell mechanics. We believe this single cell-sensitive and integrated system will unlock improved, fast, and reliable cardiac in vitro tests in the future.
Keywords: elektrofyziologické jevy; Myocytes, Cardiac; analýza dat; mechanické jevy; mikroskopie atomárních sil; spřažení excitace a kontrakce; Molecular Imaging; Electrophysiological Phenomena; molekulární zobrazování; vápníková signalizace; kardiomyocyty; Data Analysis; Excitation Contraction Coupling; Microscopy, Atomic Force; Calcium Signaling; Mechanical Phenomena